COMPETITIVENESS AS AN ECONOMIC CATEGORY - I. Timonina (Вестник Северо-Кавказского федерального университета, 2022)
The article aims at identifying the key components forming the economic content of the category «competitiveness». While achieving this goal, there was defined the main components of the competitiveness nature formed under the progressing competition, as a core environment for the competitiveness of an enterprise. That gave the possibility to identify the key factors influencing the competitive behavior of a business actor. The content of the category competitiveness is complex and depends on the scale and characteristics of the functioning object to which it is applied, namely: a product, enterprise, region or country. Moreover, it is advisable to study competitiveness and its characteristics referring to the level of functioning object analyzed. Several levels are distinguished: micro-, meso- and macro- or global.substantiated, when modeling the competitive behaviour of an enterprise, which is decisively influenceunstable socio-economic factors, including the market environment ofthe functioning business it is advis It is d by able to take into account its resources, which in general can be attributed: production, inancial and labor.